PEMBELAJARAN MATEMATIKA SMP DENGAN PENDEKATAN APTITUDE TREATMENT INTERACTION BERBASIS PORTOFOLIO - Sutama Sutama (MAJALAH ILMIAH PEMBELAJARAN, 2009)
This research and development aimed to compile model study of mathematics inSMP with interaction treatment aptitude (ATI) approach based on portfolio. Datais e collected by observation, interview, and FGD. The research participation isteachers, students, educationist, and policy makers. This research is located in fourpublic SMP and four SMP private sector of Surakarta. The data is analyzed usinginteractive cycle of data collecting, reduction data, data presentation, andwithdrawal of verification or node. The research findings can be summarized thatthe development of mathematics model study with ATI approach based onportfolio and its activities is started from antecedent phase, central activity phase,and last activity phase, with the documentation of all students. Third step isconducted in immeasurable class setting, according to the model of classical,group, and individual context. A small team learning group which has fivemember of students with the difference ability (1 is high, 2 is middle, and 1lowering) with peer tutor in rotation. The antecedent activities include a) review,b) early motivation, and c) apperception.The activity focused on the development of applying concept. The last activityincludes reviewing resume items and conducting the follow-up.